Bending in HVPE grown GaN films: Origin and reduction possibilities - Paskova, Tania; Becker, Linda; Böttcher, Tim; Hommel, Detlef; Paskov, Plamen; Monemar, Bo (Physica Status Solidi (C) Current Topics in Solid State Physics, 2007)
We have studied the effects of film and substrate thicknesses on the bending and strain of thick GaN films grown by HVPE. Both experimental and simulation data, being in a very good agreement, show the highest bending at a critical film thickness slightly smaller than the substrate thickness, while the strain remains decreasing with only a small increase at much higher film thicknesses. Temperature dependent measurements allows a separation of the thermally induced component and an extrapolation of the bending to the growth temperature. The latter was found to be dependent on both the film and substrate thickness and to have a strong effect on the remaining bending of freestanding films.